The European repository landscape 2008 : inventory of digital respositories for research output in the EU - Van der Graaf, Maurits, ....-; DRIVER (Project : Europe); European Union; Stichting SURF.; Vernooy-Gerritsen, Marjan, ....- (Amsterdam : Amsterdam University Press, 2009)
It is widely acknowledged that a common knowledge base for European research is necessary. Research repositories are an important innovation to the scientific information infrastructure. In 2006, digital repositories in the 27 countries of the European were surveyed, covering 114 repositories from 17 European countries. In follow-up, this book presents the results of the 2008 survey. It shows an increasing number of respondents, but also a further diversification in the character of a repository. Repositories may be institutional or thematically based, and as such non-institutional as well. 178 Institutional research repositories and 14 thematic and other noninstitutional repositories from 22 European countries took part actively. European practices should be harmonized and the development of state-of-the-art technology facilitated. Authors, institutes and information users are stakeholders in this process. In presenting a state-of the art of developments, this book is a valuable guide for them in developing their policy on research repositories without losing contact with others. The ongoing process of widespread and diversification of digital repositories puts urgency on coherent approach, as a basic feature of repositories is the retrievability of information that may be dispersed over many of them. Continued monitoring of developments will be necessary.
"SURF Foundation"--Cover.
"This work contains descriptions of the DRIVER II project findings ... produced with the assistance of the European Union"--T.p. verso.
Includes bibliographical references (p. 26).
Keywords: Institutional repositories -- European Union countries; Digital libraries -- European Union countries